Design of Strengthening in Agile Governance: Efforts to Develop the Tourism Sector Sustainably in Dayun Sub-District, Siak Regency - Asrida Wan; Rafi Muhammad; Pane Rico Purnawandi; Wazni Wazni; Yusri Ali; Wicaksono Baskoro; Rahmat Al Fauzi (E3S Web of Conferences)
Historically, the government and local communities have long sought to develop the tourism sector so that sustainable development goals are actively pursued for the development of the tourism sector at the village and sub-district levels. This study examines the urgency of agile governance in developing the tourism sector in Dayun District, Siak Regency. This study was conducted using a qualitative descriptive method from relevant primary and secondary data sources, then analyzed using NVivo12 Plus software to answer the research questions. Based on the analysis results, this study concludes that agile governance is a crucial component that must be applied to sustainably develop the tourism sector in Dayun District, Siak Regency. Handling forest and land fire disasters can be combined with ecotourism activities in tourist village areas using the principles of agile governance, which include the development of regional information systems, the development of business-oriented community facilities, increasing community participation in tourism governance, and emphasizing the rapid resolution of problems that arise.